A Review of Smart Microgrid Architecture and Topologies - Abdulsattar S.S.; Tan C.W.; Ayob S.B.; Dahiru A.T.; Lau K.Y.; Toh C.L. (Institute of Electrical and Electronics Engineers Inc., 2025)
Microgrids are part of emerging smart power technologies that support existing power structures that are under increased demand pressures mainly using renewable energy sources (RES). Many topologies are used in forming the microgrid architecture that employs renewable energy resources for efficient power generation, dispatch, and control. This paper envisaged and viewed that microgrid topologies emanate from technologies and methods utilized in recent applications. Hence, an investigation is carried out to identify opportunities and limitations of microgrid architecture and topologies discussed in recent works. It is found hence, that hybrid architecture is given wider consideration due to the intermittent RE resources they handle and the flexible operations they have. From the hybrid architecture of microgrids, it is suggested that a hybrid storage system is also efficient and economically a better option. ?2024 IEEE.